Multiple Congenital Epulis in Alveolar Ridges of Maxilla and Mandible in a Newborn: A Rare Case Report - Nader Saki; Somayeh Araghi (Case Reports in Otolaryngology)
Congenital granular cell lesion (CGCL) or congenital epulis is an uncommon benign of the oral cavity tumor appearing at birth with typical clinical and pathologic features. It predominately affects females, mainly on the anterior maxillary alveolar ridge, and occurs usually as a single mass, although sometimes as multiple. The left side incisor area is the most common site. The etiology and histogenesis of the lesion remain obscure. Though it is a benign lesion, the tumor may cause feeding and respiratory problems if there are too large or multiple tumors. We report a case of a three-day-old, female newborn, who was referred to our hospital with multiple congenital oral swellings arising from the maxilla and mandible. The tumors caused a feeding problem and, hence, they were resected by surgical excision under general anesthesia.